Tolerance of Artemia to static and shock pressure loading - Fitzmaurice, Brianna C.; Appleby-Thomas, Gareth J.; Painter, Jonathan; Ono, Fumihisa; McMillan, Paul F.; Hazael, Rachael; Meersman, Filip (IOP Publishing, 2017)
Hydrostatic and hydrodynamic pressure loading has been applied to unicellular organisms for a number of years due to interest from food technology and extremophile communities. There is also an emerging interest in the response of multicellular organisms to high pressure conditions. Artemia salina is one such organism. Previous experiments have shown a marked difference in the hatching rate of these organisms after exposure to different magnitudes of pressure, with hydrostatic tests showing hatching rates at pressures up to several GPa, compared to dynamic loading that resulted in comparatively low survival rates at lower pressure magnitudes. In order to begin to investigate the origin of this difference, the work presented here has focussed on the response of Artemia salina to (quasi) one-dimensional shock loading. Such experiments were carried out using the plate-impact technique in order to create a planar shock front. Artemia cysts were investigated in this manner along with freshly hatched larvae (nauplii). The nauplii and cysts were observed post-shock using optical microscopy to detect motility or hatching, respectively. Hatching rates of 18% were recorded at pressures reaching 1.5 GPa, as determined with the aid of numerical models. Subjecting Artemia to quasi-one-dimensional shock loading offers a way to more thoroughly explore the shock pressure ranges these organisms can survive.